Abdikarya: Aksi dan karya nyata untuk negeri kita - Praptiningsih, Praptiningsih; Mashuri, Ayunita Ajengtiyas Saputri; Dwiharyadi, Anda; Alfarissi, Fadhil; Arkaan, M. Faturrohman; Aqilla, Hafsah; Humaira, Naffry; Rafli, Muhammad; Syari, Amellya Yunita; Adeliawan, Inaya; Hasan, Najwa Salsabila; Nanda, Rafilah Eka; Anisa, Anisa; Yasmin, Gina Mutiara; Syawalita, Naia (Pengmasku, 2025)
The concept of patriotism (bela negara) as a tangible expression of every citizen’s responsibility in preserving the sovereignty and unity of the nation. National defense is not limited to military action but also includes efforts to overcome non-physical threats such as poverty and ignorance. In this context, community service is recognized as a form of civic duty, exemplified by the ABDIKARYA 2024 program conducted by the Student Executive Board of the Faculty of Economics and Business at UPN "Veteran" Jakarta in Cilambur Village, Leuwibatu, Bogor. The program covers educational support, economic empowerment, and infrastructure development aimed at improving community welfare. A key focus is on reinforcing the implementation of the "Merdeka Curriculum" at SDN 05 Leuwibatu, promoting entrepreneurship, and fulfilling the basic needs of local residents. The article underscores the importance of collaboration between educational institutions and communities to achieve national development and realize the ideals of independence through practical solutions to local challenges. Peran bela negara sebagai wujud nyata kontribusi warga negara dalam menjaga keutuhan dan kedaulatan negara, baik dalam bentuk fisik maupun non-fisik. Konsep bela negara tidak hanya berkaitan dengan pertahanan militer, tetapi juga mencakup perjuangan menghadapi tantangan sosial seperti kemiskinan dan kebodohan. Dalam konteks ini, pengabdian masyarakat menjadi salah satu bentuk bela negara yang dilaksanakan oleh Badan Eksekutif Mahasiswa Fakultas Ekonomi dan Bisnis UPN "Veteran" Jakarta melalui program ABDIKARYA 2024 di Desa Cilambur, Leuwibatu, Bogor. Kegiatan ini meliputi pendidikan, ekonomi, dan pembangunan infrastruktur sebagai upaya meningkatkan kesejahteraan masyarakat. Fokus utama pengabdian adalah penguatan implementasi Kurikulum Merdeka di SDN 05 Leuwibatu, pemberdayaan ekonomi melalui pelatihan usaha, serta pemenuhan kebutuhan dasar masyarakat. Artikel ini menekankan pentingnya kolaborasi antara masyarakat dan institusi pendidikan dalam membangun bangsa dan mewujudkan cita-cita kemerdekaan melalui pendekatan berbasis solusi terhadap permasalahan lokal.